(untitled) (Journal of Asian Development Studies, 2025)
This study aimed to compare the health status and academic progress of day scholars and hostellers among 200 undergraduate nursing students at ZUFONAM, using a comparative analytical cross-sectional design with simple random sampling conducted from July to August 2023. The demographic analysis revealed a higher proportion of female participants (55%) compared to males (45%). Most participants (87.5%) reported moderate health status, while 78.5% exhibited good academic performance. Significant associations were found between health status and both age and gender. A moderate positive correlation (r = 0.412) was identified between academic progress and health status, with a p-value of less than 0.001. When comparing health status scores, hostellers demonstrated a significantly better health status (32.45±4.48) than day scholars (30.8±4.28), with a p-value of 0.008. Conversely, academic progress scores showed no significant difference between hostellers (32.68 ± 2.86) and day scholars (32.59 ± 2.96), with a p-value of 0.827. The findings indicate a strong correlation between health status and academic progress among participants, highlighting that hostellers have a better health status than day scholars. However, no significant difference was observed in academic progress scores between the two groups. This study highlights the significance of residential status on health outcomes, while suggesting that living arrangements may not have a substantial impact on academic performance.